1984
DOI: 10.1530/jrf.0.0710181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholinergic and adrenergic drugs on intraluminal pressures and contractility of the rat testis and epididymis in vivo

Abstract: Intravenous administration of methacholine (200 micrograms/kg) caused no changes in the seminiferous tubules of rats, but significantly increased intraluminal pressures and contractility of the caput, the corpus and the cauda epididymidis. The effect of methacholine was abolished by pretreatment with atropine (500 micrograms/kg), but not by phentolamine (400 micrograms/kg) or propranolol (400 micrograms/kg). Adrenaline (5-40 micrograms/kg), noradrenaline (5-40 micrograms/kg) and phenylephrine (100-400 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
1
23
1
1
Order By: Relevance
“…Furthermore, histochemical studies have shown that ramifications of the cholinergic and adrenergic peritubular nerves surround the smooth muscle cells in the tubular wall of the epididymis and extend into the tubular epithelium (El-Badawi and Schenk 1967). mAChR agonists induce epididymal contraction (Hib 1976;Laitinen and Talo 1981;Pholpramool and Triphrom 1984;Ventura et al 1989), and the mAChR non-selective antagonist, atropine, but not pirenzepine (M 1 -selective antagonist) decreases electrically evoked contractions in the cauda of the epididymis as previously reported (Ventura and Pennefather 1991).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, histochemical studies have shown that ramifications of the cholinergic and adrenergic peritubular nerves surround the smooth muscle cells in the tubular wall of the epididymis and extend into the tubular epithelium (El-Badawi and Schenk 1967). mAChR agonists induce epididymal contraction (Hib 1976;Laitinen and Talo 1981;Pholpramool and Triphrom 1984;Ventura et al 1989), and the mAChR non-selective antagonist, atropine, but not pirenzepine (M 1 -selective antagonist) decreases electrically evoked contractions in the cauda of the epididymis as previously reported (Ventura and Pennefather 1991).…”
Section: Discussionsupporting
confidence: 62%
“…Cholinergic agonists, such as methacholine and carbachol, induce epididymal contractions (Hib 1976;Laitinen and Talo 1981;Pholpramool and Triphrom 1984) by interacting with muscarinic acetylcholine receptors (mAChRs). mAChRs mediate most of the actions of the cholinergic neurotransmitter in the male rat reproductive tract (Miranda et al 1994(Miranda et al , 1995Pennefather et al 2000;Borges et al 2001;Ventura et al 2002;Ban et al 2002;Nadelhaft 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the cholinergic system in the epididymis has also been described. In vitro and in vivo studies have shown that cholinergic agonists induce epididymal contraction (Laitinen and Talo, 1981;Pholpramool and Triphrom, 1984) and data from our laboratory have identified muscarinic acetylcholine receptors (mAChR) expressed along rat epididymis (Maró stica et al, 2001). In this latter study, m2 mRNA was detected in both caput and cauda epididymis, while m3 mRNA was only identified in the cauda epididymis.…”
Section: Introductionmentioning
confidence: 64%
“…Malgré l'existence de synapses axo-axonales entre les deux systèmes sympathiques [8] et la preuve pharmacolo gique de récepteurs myocytaires à l'acétylcholine et à la noradrénaline [9], le rôle joué par l'innervation cholinergique demeure incertain. Avant tout vasomotrice, on lui attribue un rôle de répresseur faible dans les contractions expulsives du muscle épididymaire [10.…”
Section: Discussionunclassified